2016
DOI: 10.18203/2319-2003.ijbcp20163222
|View full text |Cite
|
Sign up to set email alerts
|

Study to assess knowledge, attitude and practice regarding swine flu vaccine amongst medical students

Abstract: Its symptoms are similar to those of influenza in general. It includes fever, cough, sore throat, body aches, headache, chills and fatigue. The flu can make chronic health problems worse. India is ranked 3rd among the most affected countries for cases and deaths of swine flu globally. 6,7 The highest number of cases were reported in 2009 (27,236), followed by 2010 (20,604) and 2012 (5,054 cases). The highest number of swine flu deaths took place in 2011 (1,763), followed by 2009 (981) and 2012 (405). 7 In 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This could be because acquisition of knowledge of influenza and its prevention may not necessarily translate to compliance by swine industry workers in the study areas. This is similar to previous studies which reported poor correlation between knowledge of strategies for prevention of influenza and practice of such strategies (Kumar et al, ; Solunke, Dharmadhikari, Jaju, Pawar, & Gurung, ). Knowledge about influenza prevention and ability to recognize influenza in humans and pigs would therefore contribute to reduction of transmission of influenza in the West African swine industry only if pig handlers routinely practise relevant preventive measures.…”
Section: Discussionsupporting
confidence: 92%
“…This could be because acquisition of knowledge of influenza and its prevention may not necessarily translate to compliance by swine industry workers in the study areas. This is similar to previous studies which reported poor correlation between knowledge of strategies for prevention of influenza and practice of such strategies (Kumar et al, ; Solunke, Dharmadhikari, Jaju, Pawar, & Gurung, ). Knowledge about influenza prevention and ability to recognize influenza in humans and pigs would therefore contribute to reduction of transmission of influenza in the West African swine industry only if pig handlers routinely practise relevant preventive measures.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted on medical students in Latur, Maharashtra, practices of H1N1 vaccination were 12% in spite of 82.2% knowledge about availability of vaccine. [ 16 ] In a study conducted in Greece on medical students, only 8% had been vaccinated. [ 17 ] In a study done in China, vaccination rate among general population was found to be 10.8%.…”
Section: Discussionmentioning
confidence: 99%